PENGARUH PENGGUNAAN ALAT PERAGA PELUANG PUTARAN PADA MATERI PELUANG TERHADAP HASIL BELAJAR SISWA - Yensi Widiyawati; Indah Widyaningrum; Helni Indrayati (Universitas Muhammadiyah Semarang, 2019)
The formulation of the problem in this study is whether there is the influence of the use of props the opportunity to turn on the material opportunities for learning outcomes of students in class VIII SMP Negeri 8 Pagaralam..?. the porpuse of this research is to find the influence of the matter opportunities in matter opportunities of the result of student learning. The method research used is the experimentel method with Pretes-postest control group desain. sampel in class experiment VIII.C class of the students the 30 and 70,56 while the sampel in class VIII.E control of the cclassroom and the number of students 30 and include 64,83. The teachnique of the collection of the data used as documentation and tests. T test data using analysis technique to that class of his experiments wit value s namely 12,06 while to that class of control with new value s namely 12,31 in a cantcount 1,88 > ttable 1,69, then H0 rejected dan Ha the study received reseived that hypothesis. So in conclusion any impact the use of props opportunities round on the subject matter of the results off student learning.